THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT RSU ROYAL PRIMA MARELAN - Aldrian Saragih; Andre Fitriano; Jesra Jepanes Tarigan; Viviana Sari Zakaria; Ismail Nasution (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to determine the influence of Leadership Style, Work Environment and Work Discipline on Employee Performance at RSU Royal Prima Marelan. The population of this study was 240 and the sample was calculated using the Slovin formula, resulting in 71 respondents. The method in this research is a quantitative technique. The data collection techniques used were surveys and questionnaires. For data analysis techniques in this research, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis tests, T tests, F tests and coefficient of determination (R2) tests were used using SPSS Windows version 21.0. Based on the research results, it shows that the results of the t test for the Leadership Style variable (X1) do not have a partially significant effect on employee performance with a Sig value. 0.121 > 0.05, the Work Environment variable (X2) has a partially significant effect on Employee Performance with a value of Sig. 0.010 < 0.05, and the Work Discipline variable (X3) has a partially significant effect on Employee Performance with a value of Sig. 0.000 < 0.05. Meanwhile, the results of the F test show that Leadership Style, Work Environment and Work Discipline on Employee Performance have a positive and significant effect simultaneously on employee performance at RSU Royal Prima Marelan with a sig value of 0.000<0.05.